Soft rot pathogen Dickeya dadantii 3937 produces tailocins resembling the tails of Peduovirus P2 - Borowicz, Marcin; Krzyżanowska, Dorota M.; Narajczyk, Magdalena; Sobolewska, Marta; Rajewska, Magdalena; Czaplewska, Paulina; Węgrzyn, Katarzyna; Czajkowski, Robert (Frontiers in Microbiology, 2023)
Tailocins are nanomolecular machines with bactericidal activity. They are produced by bacteria to contribute to fitness in mixed communities, and hence, they play a critical role in their ecology in a variety of habitats. Here, we characterized the new tailocin produced by Dickeya dadantii strain 3937, a well-characterized member of plant pathogenic Soft Rot Pectobacteriaceae (SRP). Tailocins induced in D. dadantii were ca. 166 nm long tubes surrounded by contractive sheaths with baseplates having tail fibers at one end. A 22-kb genomic cluster involved in their synthesis and having high homology to the cluster coding for the tail of the Enterobacteriophage P2 was identified. The D. dadantii tailocins, termed dickeyocin P2D1 (phage P2-like dickeyocin 1), were resistant to inactivation by pH (3.5 -12), temperature (4 -50 ºC), and elevated osmolarity (NaCl concentration: 0.01 -1 M). P2D1 could kill a variety of different Dickeya spp. but not any strain of Pectobacterium spp. tested and were not toxic to Caenorhabditis elegans.